Application of Chemometrics in Simultaneous Spectrophotometric Quantification of Etophylline and Theophylline: The Drugs with Same Chromophore: Chemometrics in Simultaneous Spectrophotometric Determination - Kinjal R Patel; Laxman M Prajapati; Amit K Joshi; Mahammadali L Kharodiya; Jimish R Patel (Iranian Journal of Pharmaceutical Sciences, 2013)
Chemometric techniques in spectral analysis have gained importance in the quality control of the drugs mixtures and pharmaceutical formulations containing two or more drugs with overlapping spectra. Since theophylline and etophylline have common chromophore, they cannot be analyzed simultaneously using conventional UV methods. Simultaneous spectrophotometric determination of etophylline and theophylline was performed by partial least-squares (PLS) and principal component regression (PCR) methods. The absorbance values in the UV-Vis spectra were measured for the 71 wavelength points (from 230-300) in the spectral region 200-400 nm considering the intervals of 1 nm. The accuracy and the precision of the methods were determined and validated by analyzing synthetic mixtures of the drugs. The numerical calculations were performed with the ‘Unscrambler 10.3 X software. The calibration ranges were found to be 6-30 μg/ml for etophylline and 2-10 μg/ml for theophylline. The chemometrics analysis methods were satisfactorily applied to the simultaneous determination of etophylline and theophylline in the tablet dosage form.